MENELISIK HUKUM ADMINISTRASI NEGARA SEBAGAI PERLINDUNGAN DAN PENGELOLAAN LINGKUNGAN HIDUP : Fadlan Kalma - Kalma, Fadlan (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2022)
This study aims to examine the state administrative law in environmental protection. State administrative law in environmental protection is carried out in the form of supervision, enforcement of administrative sanctions, and State Administrative lawsuits. The use of environmental administration law enforcement instruments is carried out by government agencies as well as by the community or civil law entities. Administrative sanctions are instruments used in the context of law enforcement in the administrative environment. The administrative sanctions against environmental law enforcement in the implementation of environmental permits are written warnings, government coercion, freezing of environmental permits, and revocation of environmental permits. The research method used is normative legal research.